(untitled) - Aamir Khan; Waqar Hussain; Dr Raham Zaid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The aims of the study were to determine the relationship between job satisfaction of secondary school teachers, their dispositions, and students’ academic achievement. It was a correlational study. The population of the study consisted of all the secondary school teachers in the Lahore district. Over 600 educators were chosen to participate. To even things out, we chose 300 educators to work in the public school system and another 300 educators to work in the private school sector. Two instruments of the like type were employed to collect the information. Descriptive statistics like means and standard deviations were used to analyse the data, while t-tests and analysis of variance were used to look for demographic and ethnic differences in how teachers felt about their jobs. The study’s findings suggested a robust connection between teachers’ work satisfaction and student progress. It was also shown that there was a moderate link between how teachers felt and how well their students did in school.